2021
DOI: 10.3389/fmicb.2021.652642
|View full text |Cite
|
Sign up to set email alerts
|

Discerning the Antimicrobial Resistance, Virulence, and Phylogenetic Relatedness of Salmonella Isolates Across the Human, Poultry, and Food Materials Sources in Malaysia

Abstract: Salmonella enterica subspecies enterica serovar Enteritidis is one of the major foodborne zoonotic pathogens globally. It has significantly impacted human health and global trade. In this investigation, whole-genome sequencing was employed to determine the antimicrobial resistance (AMR) pattern of a collection of Salmonella Enteritidis isolated from humans, poultry, and food sources. The study also investigated the virulence genes profile of the isolates as well as the phylogenetic relationships among strains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Many studies have observed the rate at which foodborne pathogens are acquiring resistance to tetracycline and other commonly used antimicrobials in the food chain, which is a cause for concern. In the same vein, Zakaria et al have also reported a high rate of tetracycline resistance among Salmonella isolated from poultry meat [ 8 ]. S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have observed the rate at which foodborne pathogens are acquiring resistance to tetracycline and other commonly used antimicrobials in the food chain, which is a cause for concern. In the same vein, Zakaria et al have also reported a high rate of tetracycline resistance among Salmonella isolated from poultry meat [ 8 ]. S .…”
Section: Discussionmentioning
confidence: 99%
“…It is also frequently incriminated in foodborne outbreaks [ 6 ]. In recent years, the world has been witnessing the emergence of invasive nontyphoidal Salmonella lineages with an extended multidrug-resistance range [ 7 , 8 , 9 ]. The emergence, although variable, represents a major public health concern, especially in Asia and Sub-Saharan Africa [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella infection remains a major health concern that is common in poultry and is transmitted to humans through the food chain [31][32][33]. It seriously endangers the health of humans and poultry as well as the development of the poultry industry and the economy [34].…”
Section: Discussionmentioning
confidence: 99%
“…The panel of antimicrobial impregnated discs (Oxoid, USA) include aminoglycosides, ansamycins, carbapenems, cephalosporins, cephalosporins+beta lactamase inhibitors, fluoroquinolones, folate pathway inhibitor, fucidanes, glycopeptides, glycylcyclines, lincosamides, nitrofuran, oxazolidinones, penicillin, penicillin+beta lactamase inhibitors, phosphonic acids, polymyxins, streptogramins, and tetracyclines to determine resistance or susceptibility of the isolates to the drugs. 21 To avoid overestimation, the isolates with the zone of inhibition within the intermediate range were susceptible. Escherichia coli ATCC 25922 was used as a control according to the CLSI standard.…”
Section: Methodsmentioning
confidence: 99%